Applicability Analysis of Two Comprehensive Drought Meteorological Indexes in Corn Growth Period of Liaoning Province - CAO Yongqiang; ZHAO Zimeng; ZHANG Dan; REN Bo (Renmin Zhujiang)
As an important means of drought monitoring, the drought index is of significance for accurate monitoring of drought evolution characteristics during crop growth, improving agricultural drought prevention and mitigation capabilities, and promoting high and stable crop yields.Liaoning Province is an important grain producer in northeast China, and drought is the main meteorological hazard causing erratic corn production in the region.By employing Liaoning as the study area, the basic meteorological data of 19 meteorological stations from 2001 to 2020 are selected.Meanwhile, the drought meteorological composite index (CI) and meteorological drought composite index (MCI) are calculated to compare and analyze the differences between the two drought indices in drought monitoring during the corn growth period in Liaoning in terms of rainfall, average temperature, drought days, drought intensity, drought frequency, and drought event evolution characteristics, with their applicability analyzed.The results show that the precipitation and temperature trend in Liaoning in recent years is 22.37 mm/10a and 0.45 °C/10a respectively.In corn growth periods, the drought frequency of CI and MCI indices is in the order of pre-growth frequency＞late-growth frequency＞mid-growth frequency, and the drought days and frequency monitored by CI are higher than those by MCI.In spatial distribution, the drought frequency in west and south Liaoning is higher than that in other regions.By comparing the evolution characteristics of drought events with CI and MCI indices, CI shows that the drought intensity is large with long duration and much more unreasonable transition.Meanwhile, MCI has better duration and stability, but its drought intensity is low.Additionally, both the drought indices can reflect the spatio-temporal drought evolution in Liaoning, but their spatial applicability is different.CI is more suitable for drought monitoring in western and northern Liaoning, and MCI is more suitable for drought monitoring in eastern and southern Liaoning.